Yeast Interactions in Inoculated Wine Fermentation - Ciani, Maurizio; Capece, Angela; Comitini, Francesca; Canonico, Laura; Siesto, Gabriella; Romano, Patrizia (Frontiers in Microbiology, 2016)
The use of selected starter culture is widely diffused in winemaking. In pure fermentation, the ability of inoculated Saccharomyces cerevisiae to suppress the wild microflora is one of the most important feature determining the starter ability to dominate the process. Since the wine is the result of the interaction of several yeast species and strains, many studies are available on the effect of mixed cultures on the final wine quality. In mixed fermentation the interactions between the different yeasts composing the starter culture can led the stability of the final product and the analytical and aromatic profile. In the present review, we will discuss the recent developments regarding yeast interactions in pure and in mixed fermentation, focusing on the influence of interactions on growth and dominance in the process.